Case report: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leucoencephalopathy (CADASIL) as a risk factor for central serous chorioretinopathy - Pazzaglia, Alberto; Valsecchi, Nicola; Belletti, Matteo; Guaraldi, Fabio; Fresina, Michela; Fontana, Luigi (Frontiers in Neurology, 2022)
Purpose To describe an atypical case of central serous chorioretinopathy (CSC) in a patient with cerebral autosomal dominant arteriopathy with subcortical infarcts and leucoencephalopathy (CADASIL). Methods A retrospective case report. Results A 43-year-old white man with a genetic diagnosis of CADASIL was referred to our hospital because of reduced visual acuity in his right eye (20/30). In the previous 2 months, he developed CSC with subretinal fluid (SRF) and damage to the retinal pigmented epithelium without pachychoroid and pachyvessels or known risk factors for CSC. The patient was treated with transfoveal subthreshold micropulse yellow laser (577 nm) therapy. One month later, there were no signs of SRF, and visual acuity improved to 20/20. Conclusions Cerebral autosomal dominant arteriopathy with subcortical infarcts and leucoencephalopathy (CADASIL) is a genetic condition that primarily affects vascular smooth cells in small cerebral vessels and retinal arterioles. However, we hypothesize that CADASIL could also be responsible for an alteration of the vascular smooth cells in the choroidal arterioles, leading to choriocapillaris ischemia and CSC, even in the absence of a pachychoroid spectrum.